2019
DOI: 10.1111/pala.12456
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional preservation requires fast biodegradation: thylacocephalan specimens from La Voulte‐sur‐Rhône (Callovian, Jurassic, France)

Abstract: Konservat-Lagerst€ atten are seen as snapshots of past biodiversity for a given location and time. However, processes leading to the exceptional morphological preservation of fossils in these deposits remain incompletely understood. This results in a deficient assessment of taphonomic biases and limits the robustness/relevance of palaeobiological reconstructions. Here, we report the mineralogical characterization of crustacean fossils preserved within carbonate-rich concretions from the Jurassic Konservat-Lage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 87 publications
0
21
1
Order By: Relevance
“…3A,B) from the La Voulte-sur-Rhône Lagerstätte, Callovian, France, and is housed in the palaeontology collection of the Muséum national d'Histoire naturelle (acronym: MNHN.F). The La Voulte-sur-Rhône Lagerstätte is world renowned for the diversity and quality of its fauna, especially arthropods 19,26 . Fossiliferous concretions with exceptional preservation come from marls outcropping at the Ravin des Mines locality, which are topped by 15 m of iron carbonate deposits 19 .…”
Section: Methodsmentioning
confidence: 99%
“…3A,B) from the La Voulte-sur-Rhône Lagerstätte, Callovian, France, and is housed in the palaeontology collection of the Muséum national d'Histoire naturelle (acronym: MNHN.F). The La Voulte-sur-Rhône Lagerstätte is world renowned for the diversity and quality of its fauna, especially arthropods 19,26 . Fossiliferous concretions with exceptional preservation come from marls outcropping at the Ravin des Mines locality, which are topped by 15 m of iron carbonate deposits 19 .…”
Section: Methodsmentioning
confidence: 99%
“…XRD precisely identified that cuticle and muscle fibres are preserved in fluorapatite, and epithelia-rich tissues (gills, digestive gland) in pyrite and pyrrhotite [29], Arsenopyrite is also present in muscle, as well as in the appendages, where they underlie muscular structures (figure 1e, blue). Calcite is observed in the external part of the heart, but also where no organ is morphologically preserved and in the surrounding matrix (figure 1e, green).…”
Section: Identification and Distribution Of Minerals At The Microscalementioning
confidence: 99%
“…In this context, Jauvion et al used SRS-XRFD in combination with optical and electronic microscopies, EDX, powder XRD, and speciation X-ray absorption spectroscopy, to investigate fossilisation biases in the abundant D. ingens [29]. Indirect (SEM-EDX, XRF) and direct (XRD) mineralogical characterisation allowed the authors to identify and locate the various phases comprising the fossils, showing that histologically similar tissues were replaced by the same minerals under fast biodegradation [29].…”
Section: Identification and Distribution Of Minerals At The Microscalementioning
confidence: 99%
“…Recently, it was suggested that the recurrent association of particular mineralogical phases such as fluorapatite, or Fe‐sulfides (pyrite, pyrrhotite) with specific tissues in crustacean fossils preserved within carbonate‐rich concretions from the Jurassic exceptionally preserved biota of La Voulte‐sur‐Rhône (Ardèche, France) were linked to differences in the original biochemical signal of the organic matter. [ 58 ] However, much work remains to be done to determine the fate and behavior of biogenic iron during taphonomic processes, and fully enlighten the black box of pyritization. In order to test the hypothesis presented here and determine the precise roles played by biogenic iron and iron from sediments, several lines of investigation should be undertaken combining geochemical, biological, and experimental taphonomy approaches.…”
Section: Hypothesis Testing Requires a Multidisciplinary Approachmentioning
confidence: 99%